CENTRAL ASIA IN THE TRAVEL NOTES OF F.S.EFREMOV (Scientific journal of the Fergana State University, 2024)
The article examines travel notes dedicated to the Bukhara Khanate, in which a special place is occupied by the notes of F.S. Efremov, who became the first Russian author who managed to live in Bukhara for several years and study in detail the life and customs of Central Asia. Consequently, travel notes are not a form borrowed from European tradition or a transformation of hagiographical travels, but an independent genre that formed on Russian cultural soil in the second half of the 18th century.